STUDY OF THE ALGORITHM OF SELECTION OF QUALIFIED PERSONNEL FROM THE SYSTEM IN REAL TIME ON THE BASIS OF FUZZY LOGIC (Scientific journal of the Fergana State University, 2023)
The article provides an overview of the system algorithm that helps in selecting qualified personnel from a system based on fuzzy logic in real time using the Fuzzy Logic Toolbox package in the Matlab environment, which is a product of Mathworks, by forming a Mamdani-type fuzzy logic model based on a set of important rules used to select the necessary frames from the system, and as a result, based on fuzzy sampling rules that can be included in the model of the algorithm of the master system and a three-dimensional graphical representation of this model is considered